Instilling Character Values Using Jigsaw in Teaching Grammar - Achmad Baidawi; Rabi'ah Rabi'ah; abdul Wafi (Universitas Bengkulu, 2021)
Building nation character should be always done specially by the teacher in the school bacause nation character is one of fundamental elements in preventing this nation from the attack of foreign or western cultures which are not suitable with our cultures. This study aimed at decribing how the character values inserted in teaching grammar using jigsaw and what values were inserted. The study used descriptive qualitative field research. The data obtained through observation, and interview. After analyzing the data, it was found that character values were inserted through jigsaw activity. The character values found were tolerance, democratic, curiousity, communicative, responsible. This reseach is expected to contribute to build nation character through teaching and learning process.